ENHANCING LOCAL BUSINESS VISIBILITY: EDUCATION AND LOCATION PIN PLACEMENT ON GOOGLE MAPS TO SUPPORT SMES THROUGH COMMUNITY SERVICE LEARNING IN TANAH KUNING VILLAGE - Dodi Apriadi; Wismadina; Nizhamuddin; Shalahuddin; Ferawati Usman; Rahmi Nur Islami (Jurnal Akademik Pengabdian Masyarakat Ichsan Sidrap, 2024)
Real Work Lecture (KKN) is a concrete manifestation of the duties of lecturers and students in carrying out the Tri Dharma of Higher Education, namely the aspect of service. Through community service activities in Tanah Kuning village, there is a synergy between universities and the community as a manifestation of democratic knowledge. The purpose of this service is to provide understanding to the local community about the use of technology. The service is carried out through Location Pin Installation activities on Google Maps. The results of this dedication provide digital technology that can be a very effective tool for UMKM to increase their competitiveness in the global market. UMKM can take advantage of digital technology to expand market reach, increase operational efficiency, and improve product and service quality.